Transformation of Ethnonationalist Ideology among Former the Free Aceh Movement Combatants After the MoU Helsinki Peace Agreement in Bireuen Regency - Cut Maya Aprita Sari; Novita Sari; Lianna Fitri (PT ARRUS Intelektual Indonesia, 2024)
Bireuen Regency is one of the vital base areas for the Free Aceh Movement (GAM). This movement was established in 1976 and was led by Hasan Tiro. Throughout the movement, the Bireuen district became the birthplace of influential GAM fighter figures during the Aceh conflict. While actively fighting for Indonesian independence, GAM carried the ideology of Acehnese ethnonationalism. However, after the signing of the MoU on the Helsinki peace agreement on December 15, 2005, former GAM combatants transformed into a local political party in Aceh and participated in national elections. This study is interesting to examine because this transformation aligns with the acceptance of the ideology of Indonesian nationalism. Therefore, this study aims to analyze the factors that led to the transformation of ethnonationalist ideology among former GAM combatants after the Helsinki MoU in Bireuen Regency. Using qualitative methods based on interviews, the results of this study show that four factors caused the transformation of GAM ideology: peace factors, profit orientation, comfort, compulsion, and disappointment.